FOREIGN EXPERIENCE IN REGULATING ADMINISTRATIVE PROCEDURE AS A TOOL FOR ENSURING THE ACTIVITIES OF LOCAL GOVERNMENT BODIES - Malysh, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to study the foreign experience of regulation of administrative procedure as a tool for ensuring the activities of local self-government bodies. Research methods: the chosen topic of scientific research requires the use of various scientific methods and approaches to obtain qualitative results. Therefore, the following research methods were used to solve the tasks: analysis; system method; analytical, etc. Results: the future political stability of our state, as well as the effective functioning of local self-government bodies, largely depends on the optimal introduction and implementation of the administrative procedure as a tool for ensuring the activities of local self-government bodies, the purposeof which is to guarantee a reliable and effective mechanism for making administrative decisions on the rights and interests of citizens. The main function of the administrative procedure as a tool for ensuring the activities of local self-government bodies is to ensure the effective and efficient implementation and application of the law in the public interest. Discussion: achieving a new quality of local self-government is impossible without fundamental changes in approaches to understanding the institutional and procedural foundations of political and administrative processes of local democracy at the level of local self-government. Therefore, there is no doubt that the main prerequisite for the democratic development of any country is the formation and successful development of the institution of local self-government. At the same time, the practice of reforms in the vast majority of countries at the turn of the 20th and 21st centuries has clearly shown that without the creation of a strong state, this goal is practically unattainable, and in such a situation, the task of identifying the essential characteristics of local self-government and studying the main components of its successful development by borrowing positive foreign experience in this area becomes fundamentally important and urgent. It should be emphasized that the issues of local self-government are more relevant than ever at the present stage. Ukraine’s transition to a new model of local self-government and the departure from the one that developed during the Soviet Union requires close attention and detailed study, since the largely unsystematic, ill-conceived and theoretically unjustified practice of reforming the administrative-territorial organization of society in the post-Soviet period has led to obvious negative consequences. An important factor for the development of self-government institutions is the process of globalization, which significantly changes socio-political relations, changes the principles of interaction between territorial communities, political organizations, and local self-government bodies. In order to effectively exercise the powers of local self-government at the local level, it is important to have a comprehensive tool: experience in regulating the administrative procedure as a tool for ensuring the activities of local self-government bodies.